Cytokines in pathogenesis of salmonella infection - G. F. Zheleznikova (Žurnal Infektologii, 2014)
The review examines the contemporary knowledge about immune protection mechanisms with Salmonella infection, and Salmonella ability to struggle against these mechanisms. Principal emphasis was made oncytokine system reactions of innate and adaptive immunity, described in experimental and clinical researches.